Biochemistry - Champe, Pamela C. and Harvey, Richard A. (Philadelphia J.B. Lippincott Company, 1994)
Helps students to review, assimilate, and integrate large amounts of complex information by utilizing visual resources that deliver the focus and clarification needed for mastery of difficult biochemical concepts.
Include Index and Illustration
Keywords: Biochemistry -- Clinical biochemistry